Near-field imaging of the multi-resonant mode induced broadband tunable metamaterial absorber. Issue 9 (31st January 2020) - Chen, Lulu; Sun, Liaoxin; Dong, Hongxing; Mou, Nanli; Zhang, Yaqiang; Li, Qisong; Jiang, Xiongwei; Zhang, Long
Abstract : Metamaterial absorbers with tunability have broad prospects for mid-infrared absorption applications. Abstract : Metamaterial absorbers with tunability have broad prospects for mid-infrared absorption applications. While various methods have been proposed to control absorption, how to analyse and present the physical image of absorption mechanism in depth is still expected and meaningful. Here, we present experimental spatial near-field distributions of a multi-resonant mode induced broadband tunable metamaterial absorber by using near-field optical microscopy. The absorber is constructed by a metal double-sized unit cell and a metallic mirror separated by a thin Ge2 Sb2 Te5 (GST) spacer. To clearly obtain the physical images, we used a hybrid unit cell consisting of four square resonators to produce two absorption peaks at 7.8 μm and 8.3 μm. The resonance central-wavelength exhibits a redshift while switching the GST thin film from amorphous to crystalline phase. The near-field amplitude and phase optical responses of the absorber are directly observed at absorption frequencies when GST is in both phases, respectively. This work will pave the way for the fundamental science field and inspire potential applications in optical tunable absorption control.